Conselhos escolares em situações de indisciplina e/ou violência : discursos de conselheiros em três escolas públicas - Lima, Anderson de (2016)
This investigation aims to analyze the discourses of school counselors on how to cope with indiscipline and violence at school, as well as the operation of the School Board (SB) itself. The study was carried out from theoretical perspectives, and also from empirical investigation, in three public schools from São Paulo state, two of which are state schools, and one is a municipal school. It is characterized for being a qualitative study, using two methodological instruments: documental analysis (minutes of the SB meetings) from 2012 to 2014, and individual interviews conducted in 2014 with representatives from different segments of the SB (principal; teachers; parent stalf member guardian, and student). Two categories of analysis were drawn: the outline of conceptions about the SB itself and its operation; and what is understood by indiscipline and violence at schools, and the discussions about these situations presented by the collegiate at the surveyed schools. The hypothesis that both school counselors and educators in general have great difficulty in dealing with issues of indiscipline and violence at school, especially in a democratic way, was proven. There was no pretension in generalizing the analysis to a country with continental scope, and huge differences and diversities - after all, the school counselors were living in two cities in the interior of São Paulo - but, by listening to their speeches, it is possible to conclude that this difficulty was the result of two concepts that must be overcome: certain accommodation from some educators and counselors that led to same traditional school practices elated to indiscipline and violence, which were never questioned simply because there is not anything new to replace what is already done for years in a row; and certain negligence by the school, which is the failure to create opportunities for further discussions and reflections (both individual and collective) about the subject, committing all those involved with it.